Maternal mortality in Brazil, 1980 - Siqueira, Arnaldo Augusto Franco de; Tanaka, Ana Cristina d'Andretta; Santana, Renato Martins; Almeida, Pedro Augusto Marcondes de (Revista de Saúde Pública, 1984)
Brazilian maternal mortality is studied on the basis of official statistics from the country's various geographical regions, including especially the State of S. Paulo (Brazil). 1980 was chosen because of the possibility of working with data from the Population Census of that year. The principal causes of death in Brazil were found to be, in the following order: hypertensive states, haemorrhage, puerperal infections and abortion. In S. Paulo, where the fourth digit of the IDC is used, the first cause of death was eclampsia. The second was haemorrhage and the third the infections, whether due to or associated with pregnancy. As for age, one observed that the lowest maternal mortality rate occurred in the 20 to 29-year-old age group, the rate for 15-19 being slightly higher and increasing gradually in the age groups 30-39 and 40-49 years of age. It must be stated that it was not possible to analyse the rates for the 10 to 14 and over 50 age groups because of the lack of data on livebirths. However, there were 18 and 4 deaths respectively in those two groups which shows that at the extreme limits of the reproductive age there exists a not inconsiderable loss of life, mainly in the case of girls (adolescents) who are not taken into consideration at the present time in the prevailing health programs. On comparing these data with those of other countries it was found that the majority of deaths are avoidable and that it should be possible to reduce the number considerably by means of better assistance to women, and by the use of the techniques and resources which are already available.